(untitled) (Raparin Journal of Humanities (RJH), 2023)
Marketing of agricultural products is the main factor for the continuity of dealing in the production of any crop or not, and it has an important role in encouraging farmers and urging them to improve the quality of their production; Which leads to an increase in demand, and then activates this cycle of the economic cycle. Muslim jurists, in the past and in recent times, talked about rules relating to the market, marketing operations, its organization and control, and the supervision of all economic operations in it. On the other hand, the parliament in the Kurdistan Region - Iraq spoke about the process of marketing agricultural products through some articles in the law on agricultural development issued in “2008 AD” No. “4”, under the title “Law for the Protection and Development of Agricultural Production in the Kurdistan Region – Iraq”. This research evaluates the legal articles relating to marketing of agricultural products contained in the Law "Protecting and Developing Agricultural Production in the Kurdistan Region - Iraq" in the light of Islamic jurisprudence; This is in terms of the extent to which those articles agree with Islamic jurisprudence. The first topic is devoted to the concept of agricultural marketing, its elements, and objectives. In the second topic, light was shed on the texts related to the marketing of agricultural products contained in the Law “Protecting and Developing Agricultural Production in the Kurdistan Region - Iraq”, then the research showed the most important criteria for agricultural marketing in Islamic jurisprudence, and then compared and evaluated the legal texts contained in the said law in Islamic jurisprudence. At the end of the research, the researcher reached a set of conclusions, including: that what was stated in the law on “Protection and Development of Agricultural Production in the Kurdistan Region - Iraq” about marketing agricultural products is a good thing; However, it is not sufficient on the subject, as compared to Islamic jurisprudence, it shows that what is stated in it is much less than what was stated in Islamic jurisprudence on this subject.